Unifikasi Kalender Hijriyah Umat Muslim di Indonesia - Alvionita Julianti; Dhiauddin Tanjung (Astroislamica: Journal of Islamic Astronomy, 2023)
The debate about the unification of the Muslim Hijriyah calender in Indonesia has often been the subject of controversy throughout the years. These conditions are accurate in accordance with the principles of the Hijri Calender at the time of determining the beginning of the Hijri month. Muslims in Indonesia other than those who have adopted a permanent Hijri calender which is aligned with Shari’a and science.  With this one Hijri calender reference togetherness in worship can be established for all Muslim communities in Indonesia. In Indonesia itself there are several schools and methods to determine the beginning of the Hijri month. Including Nahdathul Ulama and Muhammadiyah in their determination using the reckoning and rukyat methods. The government should organize seminars and national conferences on the unification of the Hijri calender in Indonesia so that the desire for no difference between the determination of the beginning of the month for worship will be formed.